Susceptibility of hybrid grouper (epinephelus fuscogutattus ? × epinephelus lanceolatus ?) to vibrio harveyi VHJR7 - Isabella Ebi,; Mohammad Tamrin Bin Mohamad Lal; Julian Ransangan; Annita Yong Seok Kian (BIOFLUX SRL, 2018)
The susceptibility of hybrid grouper (Epinenephelus fuscoguttatus × Epinephelus lanceolatus)to Vibrio harveyi VHJR7 at three different concentrations of bacteria (8.4 ×10^4 (T1), 1.3 × 10^5 (T2), and 1.7 × 10^ 5 (T3) c.f.u. g^-1 body weight, respectively) was investigated. Fish were cultured in 150 L tankwith 7 individuals per tank and duplicated. It was then observed for any signs of abnormalities due to infections and mortalities were recorded up to 10 days of post-challenge. Cumulative mortality of hybrid grouper ranged from 0 to 57.1%. The lethal dose 50% (LD) of V. harveyi to hybrid grouper was 1.6 x 10^5 c.f.u g-1body weight. Red blood cell (RBC) and white blood cell (WBC) count of fish decreased as the bacterium concentration injected increases. The hybrid grouper is susceptible to V. harveyi VHJR7 at highdoses.